2021
DOI: 10.1002/nop2.1033
|View full text |Cite
|
Sign up to set email alerts
|

Work‐life balance of expatriate nurses working in acute care settings

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Considering the quality of work-life of nurses, several studies (26)(27)(28)(29)(30)(31)(32) have indicated poor quality of work life levels in similar with the findings in this study. Aspects identified in this study such as training and development, relationship between team members, job satisfaction, and work environment were identified to be more influencing factors related to the quality of work-life in similar to the previous study in Saudi Arabia (26).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Considering the quality of work-life of nurses, several studies (26)(27)(28)(29)(30)(31)(32) have indicated poor quality of work life levels in similar with the findings in this study. Aspects identified in this study such as training and development, relationship between team members, job satisfaction, and work environment were identified to be more influencing factors related to the quality of work-life in similar to the previous study in Saudi Arabia (26).…”
Section: Discussionsupporting
confidence: 90%
“…Aspects identified in this study such as training and development, relationship between team members, job satisfaction, and work environment were identified to be more influencing factors related to the quality of work-life in similar to the previous study in Saudi Arabia (26). In relation to organizational loyalty, poor levels of commitment were identified in the previous studies (13,25), which can be related with the low levels of quality of work-life analyzed from the findings in this study and also previous studies (26)(27)(28)(29)(30)(31)(32). Task performance, which can be analyzed from the performance of given basic nursing tasks in terms of quality and quantity, was identified to be reasonable among the nurse managers and nurses.…”
Section: Discussionsupporting
confidence: 52%
“…Nurses in government hospitals are expatriate nurses and prefer to hire female nurse expatriates, which explains that the nurses in the study settings are primarily female. Expatriate nurses from the Philippines, India, Jordan, Egypt, and other countries make up about 50 to 60% of the nurses in each of the four study settings ( Alreshidi & Alsharari, 2021 ; Ministry of Health, 2019). Regarding culture, male nurses are not permitted to work in some hospital areas, such as maternity hospitals, making them exclusively female-dominated ( Alreshidi & Alsharari, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…5 College of Nursing, University of Hail, Hail City, Saudi Arabia. 6 Faculty, College of Nursing, Shaqra University, Riyadh City, Kingdom of Saudi Arabia. 7 Faculty of Nursing, University of Tabuk, Tabuk City, Saudi Arabia.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Previous studies have indicated that emotional intelligence (EI) and self-esteem among nursing students significantly affect their academic performance, clinical competence, and general health status. For example, EI enables patients to effectively control their emotions while dealing with patients, leading to improved clinical outcomes [5,6]. Therefore, those with higher EI levels are better placed to manage the emotional demands of this profession.…”
Section: Introductionmentioning
confidence: 99%